Вимоги до маркування як один з інструментів нетарифного регулювання імпорту українських продуктів харчування в Китайській народній республіці - Сай, Л. П.; Мащак, Р. М.; Sai, L. P.; Mashchak, R. M. (Видавництво Львівської політехніки, 2022)
Проаналізовано динаміку і структуру міжнародної торгівлі українськими продуктами харчування з Китаєм. Досліджено інструменти китайської нетарифної торгівельної політики щодо імпорту продуктів харчування і їхній вплив на торгівлю з Україною. Розглянуто китайські нормативні акти і стандарти, що встановлюють вимоги до продуктів харчування. Описано процес акредитації іноземних виробників у Китаї. Розглянуто сутність і функції маркування, дано його класифікацію за певними ознаками. Досліджено вимоги Китаю щодо маркування продуктів харчування.

The article analyzes the dynamics and structure of international trade in Ukrainian food products with China. The opportunities of Ukrainian food producers to meet the demand of Chinese consumers are considered. The tools of the Chinese non-tariff trade policy regarding the import of food products (licenses, certificates of quality or compliance, certificates of origin, quality standards, requirements for packaging and labeling, legislative acts, sanitary and phytosanitary requirements) and their impact on trade with Ukraine are determined. Chinese regulations and GB state standards, which establish requirements for the safety of food and agricultural products, are considered. The process of accreditation of foreign manufacturers in China is described. Based on the analysis of literary sources, the definition of the concept of labeling is given – it is all words, descriptions, signs for goods and services, brand name, images or symbols related to food products and placed on any package, label (sticker), consumer container, counter-label, collar, label, stopper, leaflet, document, message, other packaging elements accompanying or belonging to this type of food products. The elements of labeling and its functions (informational, identification, motivational, emotional) are described, classification of food product labeling is proposed according to four characteristics (by the stage of production and sales activity at which the labeling is applied, by the content of the information on the labeling, by the breadth of coverage of product groups, by territorial scale of use).The types of product identification are considered according to the information contained in the labeling (consumer identification, assortment identification, quality identification, identification of the product belonging to a specific batch). China’s requirements for food labeling were studied, the main of which is that the labeling must meet the standards and contain complete and reliable information about the product and its manufacturer, which is necessary for the buyer to make a decision about the feasibility of purchasing it.
Labeling requirements as one of the tools for non-tariff regulation of imports of Ukrainian food products to China
Keywords: продукти харчування; міжнародна торгівля; стандарти; сертифікат; маркування; акредитація; ідентифікація; імпорт; food products; international trade; standards; certificate; marking; accreditation; identification; import; 347.122; 366.01